Analysis of ancient potteries using FT-IR, micro-Raman and EDXRF spectrometry - Başaran, Sait; Bolcal, Çetin; Güleç, Ahmet; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
This work presents the spectroscopic results of the investigations of ancient pottery remains excavated in ancient Ainos (Enez-Turkey). The FT-IR and micro-Raman spectroscopic study of the pottery remains belonging to fifth and sixth century BC allowed us to identify the mineral composition and to discuss the firing conditions. EDXRF and XRD were used as complementary techniques. To estimate the upper limit of the firing temperature of the pottery fragments, the specimens were refired up to 800 degrees C. Comparison of the second derivative profiles of the IR spectra of original and corresponding refired pottery fragments allows us to estimate the upper limit of firing temperature. Spectroscopic results indicated that the potteries were fired to a temperature less than 800 degrees C in oxidising atmosphere. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: ancient pottery; archaeometry; Inorganic pigments; IR; Micro-Raman Spectroscopy; XRF; XRD; Spectroscopy; Pigments; Art; Antik Çanak Çömlek; Arkeometri; İnorganik Pigmentler; Mikro-Raman Spektroskopisi; Spektroskopisi; Pigmentler; Sanat